2017
DOI: 10.18632/oncotarget.19087
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles and female reproductive system: how do nanoparticles affect oogenesis and embryonic development

Abstract: Along with the increasing application of nanoparticles (NPs) in many walks of life, environmental exposure to NPs has raised considerable health concerns. When NPs enter a pregnant woman’s body through inhalation, venous injection, ingestion or skin permeation, maternal toxic stress reactions such as reactive oxygen species (ROS), inflammation, apoptosis and endocrine dyscrasia are induced in different organs, particularly in the reproductive organs. Recent studies have shown that NPs disturb the developing oo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 94 publications
(148 reference statements)
2
65
0
Order By: Relevance
“…In the present study, the commercially available Au-NPs had a mean size 20 ± 5 nm as measured by the TEM. The size of metal NPs is one of the main factors that dictate whether they can cross the biological membranes and result in deleterious effects [ 46 ]. The small hydrodynamic diameter of NPs generates an increased amount of cytotoxicity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the commercially available Au-NPs had a mean size 20 ± 5 nm as measured by the TEM. The size of metal NPs is one of the main factors that dictate whether they can cross the biological membranes and result in deleterious effects [ 46 ]. The small hydrodynamic diameter of NPs generates an increased amount of cytotoxicity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fathi et al () showed the noxious effects of silver nanoparticles on the sperm and seminiferous tubules, while Qin et al () stated that cerium oxide nanoparticles adversely affected testosterone levels with a concomitant depletion of mRNA expression in steroidogenic‐related genes. Furthermore, Hou and Zhu () suggested that nanoparticles could elicit various stress responses in reproductive organs via the mechanisms of oxidative stress, apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, NPs crossed the blood-brain barrier and accumulated in the central nervous system (CNS) [59]. Later, NPs disrupted hormone secretion, such as gonadotropin-releasing hormone (GnRH), which is responsible for oogenesis, through the hypothalamic-pituitary-gonadal axis [60][61][62]. Moreover, NPs could also cross through the placenta into the fetus, causing treated mice to likely exhibit fetal inflammation, genotoxicity, apoptosis, reproductive deficiency, and immunodeficiency [60].…”
Section: Reproductive Toxicity Of Ps-npsmentioning
confidence: 99%
“…Later, NPs disrupted hormone secretion, such as gonadotropin-releasing hormone (GnRH), which is responsible for oogenesis, through the hypothalamic-pituitary-gonadal axis [60][61][62]. Moreover, NPs could also cross through the placenta into the fetus, causing treated mice to likely exhibit fetal inflammation, genotoxicity, apoptosis, reproductive deficiency, and immunodeficiency [60]. In addition, another study in Bombyx mori, an invertebrate model organism, also proved that Ag-NPs could induce reproductive toxicity.…”
Section: Reproductive Toxicity Of Ps-npsmentioning
confidence: 99%